Evaluation of Multiparametric MRI for Prostate Cancer Detection in Men with Intermediate PSA Levels (4–10 ng/mL) - AHMAD FAIZ NAJMUDDIN MOHD GHAZI (The Interventionalist Journal, 2025)
Background Prostate cancer is the third most common cancer among men in Malaysia. Due to the lack of a screening program, elevated PSA levels often raise suspicion of prostate cancer. PSA levels between 4 and 10 ng/mL, known as the "grey zone," lead to unnecessary biopsies in most of cases. Multiparametric MRI (mpMRI) with PI-RADS scoring is increasingly used as a prebiopsy tool to aid in screening within this range. Material and methods We performed a retrospective study to assess the correlation between mpMRI in men with elevated PSA levels. Men with PSA concentrations between 4-10 ng/mL, who had not previously undergone a biopsy, underwent mpMRI, followed by TRUS biopsy if necessary. The primary outcome was the relationship between the PI-RADS score and the cancer diagnosis. Secondary outcomes focused on factors associated with the diagnosis of prostate cancer. Result A total of 169 patients with PSA level of 4-10 ng/mL were included in this study. Sixty eight patients underwent mpMRI followed by TRUS biopsy. There was significant association between age and PI-RADS score in patient with prostate cancer. Prostate cancer patients are averagely older ,71-year-old compared to no cancer group,61-year-old, (p= 0.045). Significant difference between PI-RADS score and prostate cancer group with cancer patients had higher PI-RADS score (4-5) compared to non-cancer group (p< 0.001). Conclusion Multi-parametric MRI with the PI-RADS scoring system can serve as a pre-biopsy tool for patients with PSA levels between 4 and 10 ng/mL. This approach helps prevent unnecessary biopsies, provides a more objective method for diagnosing prostate cancer, and assists clinicians in making decisions for patients in this grey zone. Keywords: Prostate cancer, PSA, Multiparametric MRI